Effect of dietary protein levels on the growth of Anabas testudineus(Bloch) fingerlings - Ghosh, M; Das, S K (Indian Journal of Fisheries, 2011)
Effect of dietary protein levels on the growth of Anabas testudineus(Bloch) fingerlings